Innovative strategies in academic libraries: meeting the learning challenges of the 21st century in Africa (2019)
The paper examines innovative strategies academic libraries can adopt to address the 21st century learning challenges in Africa. The objective of the study is to identify some innovative strategies academic library can adopt to personalize library services and make library a more motivating learning environment for all category of patrons (students, teachers and researchers). The research questions include: What are the trends in technological innovations in academic libraries? What is the role of leadership in promoting academic library innovative strategies? What strategies can academic library adopt to make the library a more motivating and interesting learning environment for students? How can academic libraries strategize library services to support and encourage effective teaching and research? The paper reveals that library management or leadership is the driver of any meaningful change in an academic library. The changes include technological innovations, that is introduction of new ICT technologies in library will involve organizing training for the library personnel. That academic libraries in Africa can be better repackaged aesthetically using furniture arrangement and colours to demarcate the different section/unit with the sole aim of making the library more interesting and motivating for learning. The paper recommendations include organizing ICT and communication, interpersonal relationship skills for all library among others.